Litterfall Chemistry Is Modulated by Wet-Dry Seasonality and Leaf Phenology of Dominant Species in the Tropics - Tonin, Alan M.; Lima, Laís S.; Bambi, Paulino; Figueiredo, Monique L.; Rezende, Renan S.; Gonçalves, José F. (Frontiers in Forests and Global Change, 2021)
Litterfall has a large influence on carbon and nutrient cycling of ecosystems, particularly in light-limited forested streams, as most nutrients return in the form of litter. Although recent evidence points to the prevalence of seasonal litterfall in species-rich and evergreen tropical riparian forests, there is a limited understanding of how riparian plant diversity intersects with stream and riparian ecosystem functions. To explore this question, we investigate litterfall chemistry across wet and dry seasons and the congruence between litter traits and plant species composition of litterfall in the wet-dry tropics. Using generalized additive models, we observed consistent seasonal patterns of litterfall chemistry over two years, mostly influenced by dominant species in litterfall. While drier seasons showed litter lower in nutrients and structural compounds and higher in polyphenols, litter from wetter seasons were nutrient rich but lower in polyphenols. We also found contrasting seasonal patterns in litterfall chemistry, one showing that litterfall nutrient, structural compounds, and secondary metabolite concentrations declined in drier seasons while the other showed that mass-based litterfall inputs increased markedly in drier seasons. Our findings suggest that litterfall chemistry may be altered by shifts in the identity of dominant plant species and seasonality, possibly leading to changes in carbon and nutrient fluxes in tropical riparian ecosystems.